2021
DOI: 10.1002/fsn3.2639
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of 18β‐Glycyrrhetinic acid against myocardial infarction: Involvement of PI3K/Akt pathway activation and inhibiting Ca2+ influx via L‐type Ca2+ channels

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…These beneficial effects proved to be the consequence of GA’s ability to promote the expression of Bcl-2 and to inhibit the expression of Bax and caspase-8 through the PI3K/Akt pathway [ 180 ]. Similar inhibitory effects of the PI3K/Akt pathway were described by another study to be the cardioprotective mechanism of GA; Chu et al [ 181 ] reported that GA alleviates oxidative stress, inflammation, and apoptosis in a mice model of myocardial infarction via PI3K/Akt pathway inhibition while also decreasing Ca 2+ influx through L-type calcium channels, thus reducing cell contractility. The GA effect on Ca 2+ was also described in an ischemia-reperfusion rat model that demonstrated the significant decrease of intracellular Ca 2+ levels in cardiomyocytes through the inhibition of the late sodium current, thus improving diastolic function in patients with heart failure [ 182 ].…”
Section: Glycyrrhetinic Acidsupporting
confidence: 66%
“…These beneficial effects proved to be the consequence of GA’s ability to promote the expression of Bcl-2 and to inhibit the expression of Bax and caspase-8 through the PI3K/Akt pathway [ 180 ]. Similar inhibitory effects of the PI3K/Akt pathway were described by another study to be the cardioprotective mechanism of GA; Chu et al [ 181 ] reported that GA alleviates oxidative stress, inflammation, and apoptosis in a mice model of myocardial infarction via PI3K/Akt pathway inhibition while also decreasing Ca 2+ influx through L-type calcium channels, thus reducing cell contractility. The GA effect on Ca 2+ was also described in an ischemia-reperfusion rat model that demonstrated the significant decrease of intracellular Ca 2+ levels in cardiomyocytes through the inhibition of the late sodium current, thus improving diastolic function in patients with heart failure [ 182 ].…”
Section: Glycyrrhetinic Acidsupporting
confidence: 66%
“…As compared with GA, the metabolite 18β‐GA inhibits LTCCs with a higher sensitivity (IC 50 ≈ 30 μM) (Chu et al, 2021). 18β‐GA also inhibits Na + currents in human atrial myocytes but has no effect on cardiac voltage‐gated K + channels, such as K v 1.5 and K v 11.1 (Du et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhetinic acid has an obvious protective effect on cardiovascular, and experiments show that it can regulate the permeability of rat heart mitochondria and mediate cardiac oxidative stress and apoptosis, and improve MIRI [ 74 , 75 ]. Moreover, glycyrrhetinic acid can affect myocardial muscle strength, inhibit oxidative stress, reduce the inflammatory response, and protect the heart through PI3K/Akt pathway [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%